Pathophysiological concepts and screening of cardiovascular disease in dialysis patients - Echefu, Gift; Stowe, Ifeoluwa; Burka, Semenawit; Basu-Ray, Indranill; Kumbala, Damodar (Frontiers in Nephrology, 2023)
Dialysis patients experience 10–20 times higher cardiovascular mortality than the general population. The high burden of both conventional and nontraditional risk factors attributable to loss of renal function can explain higher rates of cardiovascular disease (CVD) morbidity and death among dialysis patients. As renal function declines, uremic toxins accumulate in the blood and disrupt cell function, causing cardiovascular damage. Hemodialysis patients have many cardiovascular complications, including sudden cardiac death. Peritoneal dialysis puts dialysis patients with end-stage renal disease at increased risk of CVD complications and emergency hospitalization. The current standard of care in this population is based on observational data, which has a high potential for bias due to the paucity of dedicated randomized clinical trials. Furthermore, guidelines lack specific guidelines for these patients, often inferring them from non-dialysis patient trials. A crucial step in the prevention and treatment of CVD would be to gain better knowledge of the influence of these predisposing risk factors. This review highlights the current evidence regarding the influence of advanced chronic disease on the cardiovascular system in patients undergoing renal dialysis.